2017
DOI: 10.3389/fphar.2017.00737
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin: A Panacea Eligible for Unrestrictive Use?

Abstract: Although artemisinin has been used as anti-malarial drug, accumulating evidence on the extended therapeutic potential of artemisinin emerges. Apart from anti-malaria and anti-tumor, artemisinin can also exert beneficial effects on some metabolic disorders, such as obesity, diabetes, and aging-related diseases. However, whether artemisinin should be applied to treatment of the wide-spectrum diseases is debating. Here, we discuss the predisposition of a raised risk of malarial resistance to artemisinin from cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In support of this possibility are results from studies showing that artemisinin and its analogs can alleviate inflammatory responses of diabetic nephropathy, reduce urinary albumin and diminish the development of diabetic nephropathy. 32,33 We next designed an experiment to examine the effect of ATM on diabetic nephropathy and found that ATM significantly reduced urinary albumin in mice, which is consistent with previous studies. The basis for ATM to significantly reduce the amount of urine remains unknown and will require further research.…”
Section: Discussionsupporting
confidence: 80%
“…In support of this possibility are results from studies showing that artemisinin and its analogs can alleviate inflammatory responses of diabetic nephropathy, reduce urinary albumin and diminish the development of diabetic nephropathy. 32,33 We next designed an experiment to examine the effect of ATM on diabetic nephropathy and found that ATM significantly reduced urinary albumin in mice, which is consistent with previous studies. The basis for ATM to significantly reduce the amount of urine remains unknown and will require further research.…”
Section: Discussionsupporting
confidence: 80%
“…The investigation of the biological activity of Artemisia species and their constituents is required to explore the full potential of diverse Artemisia species and their chemical ingredients against cancer, malaria, and infections [42]. Artemisinin can also exert beneficial effects in treatment of the wide-spectrum diseases such as obesity, diabetes, and aging-related disorders [43].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, extensive in vitro and in vivo preclinical data support the therapeutic efficacy of artemisinins in a variety of human disease conditions beyond malaria, such as cancer, diabetes, atherosclerosis, viral infections, autoimmune diseases and, not least, in neurodegenerative diseases [49]. These effects seem to be mediated by artemisininsinduced changes in several signaling pathways, that interfere with multiple hallmarks of the respective diseases and probably rely on multitarget and promiscuous interactions of artemisinins with cellular proteins [50]. However, the exact molecules and substances that directly interact with artemisinins have yet to be determined.…”
Section: Artemisinins: Chemical Structure Pharmacokinetic Behaviors A...mentioning
confidence: 99%